MATHEMATICAL MODEL OF DPKR-2 DYZEL TRAIN CAR - Kostritsa, S. A.; Sobolevska, Y. H.; Kuzyshyn, A. Y.; Batih А. V. (Science and Transport Progress, 2018)
Purpose. In order to study the dynamic phenomena arising when rolling stock moves along a rail track both in the straight and curved track sections, the article is aimed to construct a mathematical model of DPKr-2 diesel train car. It will be constructed on the basis of mechanical model of this car of Kryukiv Railway Car Building Works. Methodology. To construct a mathematical model a system of 38 differential equations of the diesel train movement is formed. When it is used a pneumatic spring in the core stage of spring suspension, its equivalent mechanical mo-del is presented as Kelvin-Voigt knot. It includes a parallel elastic element and an element of viscous friction. Rail track flexibility is taken into account by elastic and dissipative elements. During simulation it was assumed that the wheel pair and the track weight interacting with it were moving intact. Geometric inequalities of the left and right rails were accepted as disturbances when studying the forced vertical and horizontal oscillations. Findings. On the basis of the adopted mechanical model of the diesel train car we constructed the mathematical model consisting of 38 differential equations of motion . Originality. For the first time, for the DPKr-2 diesel train car we developed its spatial mathematical model taking into account the features of the interaction of individual elements of its construction and the possibilities of the rail track depression. When constructing the mathematical model, it was proposed to take into account the flexibility of the rail track by elastic and dissipative elements. Originality. The mathematical model of the diesel train car will be used for studying the dynamic phenomena and determining the dynamic loads of structural elements during operation. The study of these phenomena is necessary for optimal choice of the scheme and parameters of rolling stock equipment, in particular antivibration devices (spring suspension, horizontal, longitudinal and transverse joints of wheel pairs with the bogie frame, bogie with the body), as well as for reduction of dynamic forces acting on the elements of rolling stock construction and rail track.